Somatic Embryogenesis and Plant Regeneration from Stem Explants of Pomegranate - Jingting Wang; Xinhui Xia; Gaihua Qin; Jingwen Tang; Jun Wang; Wenhao Zhu; Ming Qian; Jiyu Li; Guangrong Cui; Yuchen Yang; Jingjing Qian (Horticulturae, 2023)
Plant regeneration through somatic embryogenesis provides a solution for maintaining and genetically improving crop or fruit varieties with desirable agronomic traits. For the fruit tree pomegranate (Punica granatum L.), despite some successful applications, the existing somatic embryogenesis protocols are limited by low availability of explants and susceptibility to browning. To address these problems, in this study, we developed an effective system for induction of high-vigor pomegranate somatic embryos derived from stem explants. The usage of stem explants breaks through the difficulty in obtaining material, thus making our system suitable for widespread commercial production. To enhance the performance of our system, we identified the optimal explants, subculture cycles and combination of basal media and plant growth regulators for each step. The results showed that inoculating stem explants onto a Murashige and Skoog (MS) medium supplemented with 1.0 mg/L 6-benzylaminopurine (6-BA) and 1.0 mg/L 1-naphthaleneacetic acid (NAA) achieved the best induction rate and growth status of pomegranate calli (induction rate = ~72%), and MS medium containing 0.5 mg/L 6-BA and 1.0 mg/L NAA was the optimal condition for the induction of embryogenic calli and somatic embryos (induction rate = ~74% and 79%, respectively). The optimal subculture period for embryogenic calli was found to be 30–35 days. Strong roots were then induced in the developed somatic embryo seedlings, which survived and grew well after transplantation to the natural environment, indicating the good vitality of the induced pomegranate somatic embryos. Together, our system provides a solution to mass somatic embryo induction and plant regeneration of pomegranate and lays a foundation for future genetic transformation and bioengineering improvement of pomegranate with favorable agronomic traits.